2021
DOI: 10.1002/tox.23333
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimetastatic activity of Momordica balsamina crude acetone extract in HT‐29 human colon cancer cells

Abstract: Plant‐derived compounds and/or extracts have proven to be beneficial for the treatment of a broad spectrum of cancers with minimal side effects. In this study, we investigated whether a crude acetone extract of Momordica balsamina (MBE) can interfere with the metastatic ability of HT‐29 colorectal cancer (CRC) cells. The phytochemical composition of MBE was determined by ultra‐performance liquid chromatography and cytotoxic effects by the MTT and acridine orange/ethidium bromide staining assays. The effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Different assays were performed to evaluate the cytotoxicity effects of the studied African plant extracts, including a crystal violet cell antiproliferation assay [ 29 ], resazurin reduction assay [ 20 , 21 , 22 , 25 , 34 ], or tetrazolium-based colorimetric cell proliferation assays such as MTT [ 14 , 16 , 17 , 19 , 23 , 26 , 28 , 29 , 30 , 31 , 33 ], MTS [ 32 ] and WST-1 [ 13 ]. There were studies where cell numbers were determined using Hoechst 33342/Propidium Iodide (PI) staining [ 12 , 18 ], trypan blue [ 24 ], or were based on the quantification of Adenosin Triphosphate (ATP), signaling the presence of metabolically active cells [ 15 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different assays were performed to evaluate the cytotoxicity effects of the studied African plant extracts, including a crystal violet cell antiproliferation assay [ 29 ], resazurin reduction assay [ 20 , 21 , 22 , 25 , 34 ], or tetrazolium-based colorimetric cell proliferation assays such as MTT [ 14 , 16 , 17 , 19 , 23 , 26 , 28 , 29 , 30 , 31 , 33 ], MTS [ 32 ] and WST-1 [ 13 ]. There were studies where cell numbers were determined using Hoechst 33342/Propidium Iodide (PI) staining [ 12 , 18 ], trypan blue [ 24 ], or were based on the quantification of Adenosin Triphosphate (ATP), signaling the presence of metabolically active cells [ 15 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The compounds had the lowest intestinal absorption of 50.312%. This can be attributed to the fact that they are both triterpenes with similar molecular formulae and their differentiation is difficult as also observed by Serala et al 36 The ligands Momordicoside I aglycone, Balsaminol E, CHEMBL468165, Charantadiol A, 3beta,25-diol, Balsaminol E and CHEMBL249658 violated the ROF with log P values greater than 5. Although the log P value, which affects the compound’s lipophilicity, is a major determining factor in a compound’s penetration across vital membranes and biological barriers, some researchers 39 argue that these rules can be done away with at least during a virtual screening protocol, because it is essential to first look for a potent molecule and once potency is validated, improved kinetics can then be sought.…”
Section: Pharmacokinetic Studiesmentioning
confidence: 75%
“…Our results are in agreement with studies that have shown the in vitro anti-schistosomal activity of triterpenes in plants such as Argemone mexicana , 35 Momordica balsamina, Actinopyga echinites , and Holothuria polii . 10 , 36 …”
Section: Resultsmentioning
confidence: 99%
“…Considering that about every fourth colon cancer patient displays distant metastases after resection [ 52 ] and cancer mortality is mainly due to metastasis lesions [ 52 , 53 ], searching for new therapeutic agents to suppress cancer cell invasion and migration is crucial. However, data from human studies regarding the effects of anthocyanins on colon cancer progression are scarce and to date, it has not yet been clarified whether anthocyanins, particularly at physiological concentrations, have an impact on cancer cell migration in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis is a multistep process that comprises cell migration from the primary tumor site, cell invasion, attachment to endothelial cells, extravasation, proliferation, and angiogenesis at the distal site [ 53 , 56 ]. Degradation of the extracellular matrix, especially collagen, mediated by proteolytic enzymes such as MMP-2 (gelatinase-A) and MMP-9 (gelatinase-B), is known to be the first step and plays a crucial role during cell migration and invasion [ 31 , 57 ].…”
Section: Discussionmentioning
confidence: 99%